An update on diagnosis of coeliac disease - Real Delor, Raúl Emilio (2016)
Celiac disease (CD) is a multisystem autoimmune condition induced by gluten in genetically susceptible individuals. The classical clinical presentation is the chronic diarrhea syndrome although there are atypical and silent forms, which may lead to diagnostic problems. Diagnosis is based on the detection of various autoantibodies, especially against tissue transglutaminase IgA, although the gold standard is the pathological examination of duodenal biopsies obtained by upper endoscopy. The absence of the HLA gene is a test used to rule CD. The response to gluten-free diet confirms this condition, which if not promptly diagnosed and properly treated can lead to serious complications.